1991
DOI: 10.3109/00498259109044402
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a hydroxy metabolite of diflunisal in rat and human urine

Abstract: 1. A new metabolite of diflunisal, a hydroxy derivative, has been identified in rat and human urine following administration of diflunisal. 2. This hydroxy metabolite of diflunisal is excreted in urine of both species as a polar conjugate, most likely a sulphate. 3. Attempts to isolate the polar conjugate in pure form were unsuccessful due to its rapid hydrolysis in the presence of acid, and organic solvents such as diethyl ether. Its breakdown product, however, was more stable and was isolated and purified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Nine of these metabolites were shown to be either mono-, or dihydroxy derivatives of the original anti-inflammatory drug molecules. The products generated by the fungi of the current study are similar to those found in the phase I metabolism of mammalsmetabolism to various hydroxylated products was shown for these pharmaceuticals (Macdonald et al, 1991;Wing Lam et al, 2007;Stülten et al, 2008;Tevell Åberg et al, 2009;Borges et al, 2010). These metabolites can be less toxic or more toxic compared to the original compounds.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nine of these metabolites were shown to be either mono-, or dihydroxy derivatives of the original anti-inflammatory drug molecules. The products generated by the fungi of the current study are similar to those found in the phase I metabolism of mammalsmetabolism to various hydroxylated products was shown for these pharmaceuticals (Macdonald et al, 1991;Wing Lam et al, 2007;Stülten et al, 2008;Tevell Åberg et al, 2009;Borges et al, 2010). These metabolites can be less toxic or more toxic compared to the original compounds.…”
Section: Discussionsupporting
confidence: 61%
“…So far, no fungal metabolites of DIF have been described in the literature. The compound showed peaks identical to those described in the literature (Macdonald et al, 1991;Dickinson et al, 1994). As in the case of DIC, the halogenated ring was untouched; MS (Paíga et al, 2015), most probably the isobutyl sidechain is hydroxylated.…”
Section: Metabolites Of Nsaidssupporting
confidence: 62%
“…The remaining 10-15% may be excreted in the bile and faeces or it may be excreted in the urine as the 3-hydroxy metabolite of diflunisal (i.e. hydroxylation in position 3 of the salicylic acid ring), identified recently in human urine by Macdonald et al (1989).…”
Section: Discussionmentioning
confidence: 99%